APPLICATION OF ELECTRICAL RESISTIVITY METHOD FOR FOUNDATION STUDIES AND GROUNDWATER INVESTIGATION AT FEDERAL UNIVERSITY DUTSINMA, KATSINA STATE, NIGERIA - Ahmed, Aminu Lawal; Basamasi, M. L.; Umar, M.; Balarabe, B. (FUDMA JOURNAL OF SCIENCES, 2020)
Geophysical investigation for engineering and environmental studies has been undertaken at the permanent site of Federal University Dutsin-ma, Katsina state. The study was aimed at assisting in the planning and development of infrastructure at the University, and also to investigate the groundwater potential of the permanent site at Turare which is less than 20km south of the current site the University occupies. Twenty-four Vertical Electrical Soundings (VES) were conducted along predetermined profiles at the permanent site in Dutsin-ma. Terrameter SAS 300 system was used for data acquisition at stations interval of 100m using Schlumberger array. Maximum current electrode separation (AB) of 200m was used. Interpretation was performed using computer software (Ipi2win and surfar7). The interpreted result was used to produce geoelectric and geologic sections. The result of the study indicated that the area is underlain by three to four subsurface layers. The resistivity of the first layer range from 25.5ðœ´m to 429.25ðœ´m with an average thickness of 2m. The layer is referred to be the superficial cover, composed of sandy, clay, silt and weathered laterite. The second Layer has resistivity values between 95.5ðœ´m to 553.2ðœ´m which is the weathered basement rock and fresh laterite in some areas/places. And the third layer has relatively low resistance ranging from 81.5ðœ´m to 240.8ðœ´m.  This layer is the fractured basement with varying thickness. The fourth layer is the crystalline basement rock with resistivity value much greater than 1000ðœ´m and infinite thickness. The investigations showed that the north-western part of the study area is
Keywords: Geoelectric section, Geologic section, Aquifer, Vertical Electric Sounding (VES), Groundwater and Foundation